Occurrence of diseases in fish used for experimental research. (December 2019) - Iaria, Carmelo; Saoca, Concetta; Guerrera, Maria Cristina; Ciulli, Sara; Brundo, Maria Violetta; Piccione, Giuseppe; Lanteri, Giovanni
The objective of the present study was to evaluate the occurrence of pathogens and diseases in laboratory fish over a 10-year period at the Centre for Experimental Fish Pathology of Sicily, University of Messina. This report also emphasizes the adverse effects of subclinical infections on research endpoints, as well as the importance of animal health with respect to welfare. Infections in fish used for research can alter experimental outcomes, increase the variability of data, and impede experimental reproducibility. For this purpose, 411 diseased fish of different species (out of a total of 2820 fish) that belonged to four marine species ( Dicentrarchus labrax, Sparus aurata, Argyrosomus regius and Mugil cephalus ) and to four fresh water species ( Danio rerio, Carassius auratus, Xiphophorus variatus and Poecilia reticulata ) were examined in this study. Our results showed that mycobacteriosis and myxosporidiosis were the most important diseases found in our research fish, and the results represent a useful tool to obtain wider knowledge on the incidence of various diseases in different fish species. Further studies in this field are necessary to improve knowledge on the state of the health of fish used for research.